Commentary: Enthusiasts for Learning: Leaders in Creativity (LEARNing Landscapes, 2012)
This commentary points to several movements in modern economies that support informal or voluntary learning. A historical context establishes reasons for the rise of professional amateurs, such as citizen scientists, community youth arts organizations, and do-it-yourself individuals and groups. Creativity marks the nature of learning among voluntary learners, as does dedication to open sourcing. Shared knowledge at the citizen/consumer level benefits everyone. Within this atmosphere, young people are drawn to follow through on problems and issues by seeking information, guidance, and demonstration from sources of expertise on the Internet, in their communities and schools, and among others similarly enthused about learning on one’s own in one’s own way.
Keywords: informal learning; volunatry learning; professional amateur; creativity; open sourcing; citizen scientist; community youth organization